Advances in nanomaterial-mediated CRISPR/Cas delivery: from lipid nanoparticles to vesicle-derived systems - Wang, Bingning; Lu, Jingyuan; Zhang, Xiaoyi; Hu, Ruoyang; Ma, Haowei (Frontiers in Bioengineering and Biotechnology, 2026)
Gene and genome editing therapies are increasingly connected with nanomaterials, which protect and transport fragile nucleic acids and CRISPR/Cas systems through biological barriers safely and accurately. This review discusses how different nanocarriers, including lipid-based, polymeric, inorganic, and vesicle-derived systems, can improve delivery efficiency, cell targeting, endosomal escape, and intracellular movement for gene and genome editing. It summarizes findings from early clinical and preclinical studies, comparing several carrier types such as ionizable lipid nanoparticles, polymeric nanoparticles, micelles, gold and silica nanostructures, and engineered extracellular vesicles. The review also explains how specific design factors, such as surface ligands, charge modification, PEGylation, and stimulus-responsive behaviors, influence biodistribution, and improve on-target efficiency while lowering immune responses and off-target effects. Ethical and regulatory concerns for in vivo editing are highlighted, along with current methods used to study nano–bio interactions. Among these carriers, ionizable lipid nanoparticles show the most advanced performance for delivering nucleic acids and CRISPR systems. However, new polymer-based and exosome-inspired carriers are progressing rapidly for repeated and targeted applications. Hybrid and responsive systems may also enable better spatial and temporal control of editing. Future research should focus on stronger in vivo potency testing, improved biocompatibility evaluation, and standardized manufacturing to ensure clinical safety and reliability.